Smoking and body fatness measurements: a cross-sectional analysis in the EPIC-PANACEA study. - Travier, N; Agudo, A; May, A; Gonzalez, C; Luan, J; Besson, H; Wareham, N; Slimani, N; Rinaldi, S; Clavel-Chapelon, F; Boutron-Ruault, M; Palli, D; et al. (2009)
OBJECTIVE: The present study investigates the cross-sectional relationship between tobacco smoking and body fatness. METHODS: This cross-sectional study consisted of 469,543 men and women who participated in the European Prospective Investigation into Cancer and Nutrition (EPIC) study between 1992 and 2000 providing anthropometric measurements and information on smoking. Adjusted multilevel mixed-effects linear regression models were used to assess the association between smoking and body fat mass. RESULTS: The analyses showed that BMI and WC were positively associated with smoking intensity in current smokers but negatively associated with time since quitting in former smokers. When compared to never smokers, average current smokers (17 and 13 cig/day for men and women, respectively) showed a lower BMI. When average former smokers (men and women who had stopped smoking for 16 and 15 years, respectively) were compared to never smokers, higher BMI and WC were observed in men, whereas no significant associations were observed in women. CONCLUSIONS: This cross-sectional study suggests that smoking may be associated with body fatness and fat distribution. Although our findings cannot establish cause and effect, they suggest that providing information and support to those who want to stop may help in preventing weight gain and therefore weaken a barrier against stopping smoking.